Editor’s Letter - Sánchez Gutiérrez, José (Mercados y Negocios, 2025)
We are pleased to present issue 56 of Mercados y Negocios, an edition that reaffirms our commitment to promoting rigorous research in management, business, and economics from a global perspective. This issue highlights the following contributions.